Post-Synthetic Derivatization of Graphitic Carbon Nitride with Methanesulfonyl Chloride: Synthesis, Characterization and Photocatalysis - Praus, Petr; Smýkalová, Aneta; Foniok, Kryštof; Velíšek, Petr; Cvejn, Daniel; Žádný, Jaroslav; Storch, Jan (Nanomaterials (Basel, Switzerland), 2020)
Bulk graphitic carbon nitride (CN) was synthetized by heating of melamine at 550 °C, and the exfoliated CN (ExCN) was prepared by heating of CN at 500 °C. Sulfur-doped CN was synthesized by heating of thiourea (S-CN) and by a novel procedure based on the post-synthetic derivatization of CN with methanesulfonyl (CH3SO2-) chloride (Mes-CN and Mes-ExCN). The obtained nanomaterials were investigated by common characterization methods and their photocatalytic activity was tested by means of the decomposition of acetic orange 7 (AO7) under ultraviolet A (UVA) irradiation. The content of sulfur in the modified CN decreased in the sequence of Mes-ExCN > Mes-CN > S-CN. The absorption of light decreased in the opposite manner, but no influence on the band gap energies was observed. The methanesulfonyl (mesyl) groups connected to primary and secondary amine groups were confirmed by high resolution mass spectrometry (HRMS). The photocatalytic activity decreased in the sequence of Mes-ExCN > ExCN > CN ≈ Mes-CN > S-CN. The highest activity of Mes-ExCN and ExCN was explained by the highest amounts of adsorbed Acetic Orange 7 (AO7). In addition, in the case of Mes-ExCN, chloride ions incorporated in the CN lattice enhanced the photocatalytic activity as well.
Keywords: derivatization; mesyl chloride; photocatalysis; sulfur; graphitic carbon nitride